Studies on the Economic Performance of Argentinean North Central Railway, a State-Funded Line, from 1889 to 1920 - Abril, María de las Mercedes; Blanco, María Beatriz (Current Topics on Mathematics and Computer Science Vol. 4, 2021)
The state funded railways in Argentina became one of the country's most important enterprises at the turn of the twentieth century, partly because of their political significance as well as their importance in the national economy. The building of a railway is an enterprise that demands large amounts of money, because of its size and complexity. The behavior of the North Central Railway is the subject of our investigation. To do so, we will use a set of variables that describe its economic performance, such as the annual series of rail kilometres, transported passengers, transported cargo (measured in tonnes), and a measure of invested capital, which we will call return. We'll employ time series analysis methodologies. These methods will allow us to check whether the Argentine government's transportation policy was implemented with a true sense of economic advantage or not.